The severe thunderstorm of 4 October 2007 in Mallorca: an observational study - C. Ramis; R. Romero; V. Homar (Natural Hazards and Earth System Sciences, 2009)
During the afternoon of 4 October 2007, a thunderstorm swept across the Island of Mallorca from southwest to northeast. Strong straight-line winds (up to 30 m/s) and heavy rain (rates up to 100 mm/h) were registered accompanying the storm. Tornadoes with an estimated intensity of F2–F3 developed nearby the city of Palma, severely affecting industrial installations. One person was killed by the impact of heavy debris while more than 10 million € in damages were attributed to the event in the industrial area only. The observed evolution of temperature, humidity, wind and pressure, as well as the sequence of radar images, reveal that a squall line was initially organized over the sea and then moved north-eastwards at an estimated speed of around 80 km/h. This paper presents an analysis of the event from an observational point of view. The aim of the study is to contribute to the characterization of these rare events in the Western Mediterranean by analyzing the observational information available for this particular extreme event. The diagnosis is aimed at helping forecasters to identify this kind of organized deep convective events and being able to issue timely warnings. The synoptic scenario shows warm and moist advection at low levels over Balearics and an upper-level trough over mainland Spain. This situation is known to be prone to deep convection in Mediterranean Spain in autumn. Radiosonde ascents from Murcia and Palma show convective instability at mid levels that can conduce to develop convection if appropriate ascents occur. A plausible lifting mechanism to trigger convection is attributed to large amplitude gravity waves, registered as short-period pressure oscillations by surface barographs.